|Version 2 (modified by malcolm.wallace@…, 10 years ago) (diff)|
Flexible Partial Application
Are there any subtle reasons for why something like the following couldn't be allowed?
> foo x y z w = ... > bar x w = foo x _ _ w
I.e. a more flexible version of partial application. This would be translated to
> bar x w = \y z -> foo x y z w
I.e a function which takes the "_" parameters in the same order they were encountered in the function application.
One can usually assume id e = e, for any e, but
id (f _ x) y === id (\y->f y x) y === f y x /= f _ x y === \z -> f z x y
Or would (f _ x) y and f _ x y maybe be different? That would fix the problem above, while introducing another.